2011
DOI: 10.1111/j.1542-2011.2011.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Intervention to Change Planned Behavior Concerning Midwife‐Assisted Out‐of‐Hospital Childbirth

Abstract: The results indicate that 'The Business of Being Born' can increase awareness of and support for the midwifery profession, and that these changes may result in increased demand for midwifery services. However, proactive efforts must be taken to ensure that the film reaches its target audience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Participants in these studies did not yet have children but reported future childbirth intentions, underscoring opportunities for people to become more informed about birth settings. Participants in one study reported a significant increase in interest for home and birth center settings after exposure to The Business of Being Born , either for themselves or recommending such an option to their family and friends 54 …”
Section: Resultsmentioning
confidence: 99%
“…Participants in these studies did not yet have children but reported future childbirth intentions, underscoring opportunities for people to become more informed about birth settings. Participants in one study reported a significant increase in interest for home and birth center settings after exposure to The Business of Being Born , either for themselves or recommending such an option to their family and friends 54 …”
Section: Resultsmentioning
confidence: 99%
“…For some researchers, the ways in which television reflects or reinforces social norms around birth and motherhood is at issue (O'Brien Hill 2014;Sears et al 2011;Morris et al 2010;Verena Siebert 2012;Feasey 2012), still others focus on how women make sense of televised birth (De Benedictis 2016;Bessett et al 2018;Hall 2013). In a minority are those who research the role of television in health education and its potential for public health interventions (Kavanagh et al 2012;Hans et al 2011). These findings are summarised in Table 1.…”
Section: Results: a Map Of The Fieldmentioning
confidence: 99%
“…This is partly because of the nature of the "audiences" that have been researched. Experimental psychology studies have relied on student populations, sometimes all female (Vitek et al 2018), sometimes mixed sex (Hans et al 2011;Kavanagh et al 2012). While this practice is not uncommon, questions remain about the representativeness of student samples and the transferability of findings to the general population (Paul H.P.…”
Section: Production Representation or Receptionmentioning
confidence: 99%
See 2 more Smart Citations